A Study on Financial Performance of District Co-operative Bank Ltd., Pauri Garhwal - Agarwal, Priyanka (Journal of Commerce and Trade, 2018)
In the modern oriented economy, finance is one of the basic foundations of all kinds of economics activities. Finance statements are prepared primary for decision making. This study mainly focuses on investigating the major factors that influence District Co-operative Bank financial performance. The Bank has been maintaining fair financial performance and further it can improve if the bank concentrates on with the overall service quality of their product and maintain proper fund. This paper is descriptive in nature, and data has been collected through secondary sources. The major findings of the study are that District Co-operative Bank Pauri Garhwal has been maintaining fair financial performance and further it can improve. The study also identified specific areas for District Co-operative Bank Pauri Garhwal to work on which can ensure sustainable growth for the bank. I try to show the differences between financial performances of District Co-operative Bank Pauri Garhwal over the last 4 year periods. Classification-JEL : E21, E44, E59, G21